2012
DOI: 10.3390/toxins4110991
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic Potential of Aspergillus Species Occurring on Maize Kernels from Two Agro-Ecological Zones in Kenya

Abstract: Two agro-ecological zones in Kenya were selected to compare the distribution in maize of Aspergillus spp. and their toxigenicity. These were Nandi County, which is the main maize growing region in the country but where no human aflatoxicoses have been reported, and Makueni County where most of the aflatoxicosis cases have occurred. Two hundred and fifty-five households were sampled in Nandi and 258 in Makueni, and Aspergillus was isolated from maize. Aspergillus flavus and A. parasiticus isolates were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 40 publications
6
75
2
2
Order By: Relevance
“…The current findings on the abundance of A. flavus L-strain contradict those of Okoth et al (2012) who reported that A. flavus S-strain was the most predominant in maize obtained from Makueni region of Kenya. A previous study in Eastern Kenya by Probst, Njapau and Cotty (2007) observed a higher incidence of A. flavus S-strain (71.8%), followed by A. flavus L -strain (28.2%) and lastly A. parasiticus (2.1%).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The current findings on the abundance of A. flavus L-strain contradict those of Okoth et al (2012) who reported that A. flavus S-strain was the most predominant in maize obtained from Makueni region of Kenya. A previous study in Eastern Kenya by Probst, Njapau and Cotty (2007) observed a higher incidence of A. flavus S-strain (71.8%), followed by A. flavus L -strain (28.2%) and lastly A. parasiticus (2.1%).…”
Section: Discussioncontrasting
confidence: 56%
“…Predominance of A. flavus L-strain in the current study could be attributed to the fact that the climatic conditions during the study period were not harsh to favour A. flavus S-strain over other members of Aspergillus section Flavi. The high occurrence of Aspergillus section Flavi in this study indicates a risk of aflatoxin poisoning when conditions are favorable as observed by Probst et al (2007) since Aspergillus section Flavi, have been reported as the main contaminants of maize from Eastern regions, Kenya (Okoth et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This could be attributed to unfavourable climatic conditions for the fungal growth and, to a lesser extent, presence of lowaflatoxin-producing L strains of Aspergillus found in their soils [20]. A survey of maize collected from local mills in Bungoma and Kisii found a low proportion of samples contaminated above legal limits, with only 2% and 8%, respectively, exceeding the limit [21], results that were much lower than in the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…These isolates are known to produce high levels of aflatoxins in maize grain [19,20]. For inoculation of the field trials in South Africa, three toxigenic strains of A. flavus (MRC 3951, MRC 3952, and MRC 3954) were obtained from the Medical Research Council's Programme on Mycotoxins and Experimental Carcinogenesis unit (MRC-PROMEC, Tygerberg, South Africa).…”
Section: Inoculum Production and Field Inoculationmentioning
confidence: 99%